Genetic Basis of Agronomic Differences between a Modern and a Historical Spring Wheat Cultivar. Issue 1 (1st January 2014) - Sherman, J. D.; Martin, J. M.; Blake, N. K.; Lanning, S. P.; Talbert, L. E.
ABSTRACT: Modern spring wheat ( Triticum aestivum L.) cultivars are typically of semidwarf growth habit and have higher yield potential than their predecessors. Since the introduction of reduced height alleles, breeders have selected for higher grain yield and improvements in other traits. The objective of this project was to determine the genetic basis for differences between a modern spring wheat cultivar 'McNeal' with Rht‐D1b for semidwarf habit and a historically important standard height cultivar 'Thatcher'. A recombinant inbred line (RIL) population with 160 lines, including 80 in each height class, was tested in five environments in Montana. The Rht‐D1 locus explained 90% of the height variation. The Rht‐D1b allele had positive pleiotropic effects on grain yield and productive tiller number, explaining 73 and 33% of the respective variation. Negative pleiotropic effects occurred for grain protein, seed weight, and test weight, as Rht‐D1 explained 42, 24, and 7% of the variation within the RIL. Favorable alleles at quantitative trait loci (QTLs) of lesser effect than Rht‐D1 were more often contributed by McNeal for seed size and test weight than by Thatcher. A total of 17 epistatic interactions were observed, of which nine involved Rht‐D1 . Our results indicate that alleles for semidwarf habit explain most of the improvement in grain yield. Selection of favorable alleles at other loci has helped to mitigate negative pleiotropic effects of Rht‐D1b . Our results provide insight into the genetic basis of wheat improvement through breeding.